THE WAY OF JAVANESE PEOPLE MAINTAIN IN THE JAVANESE LANGUAGE IN DUSUN KAMPUNG BANJAR-LABURA - Diah Ekowati Utami; I Wayan Dirgeyasa; Rahmad . Husein (LINGUISTIK TERAPAN, 2022)
ABSTRACT This research deals with describing Javanese language maintenance in Dusun Kampung Banjar Labuhanbatu Utara. This research is conducted by using qualitative method. This research aims to examine the way of Javanese people maintain the Javanese language in Dusun Kampung Banjar. The data were collected from nine persons (male and females) of Javanese people using the observation and interview. The observation was used to examine researcher found there are some ways of Javanese people maintain the Javanese language. The data were analyzed by Miles, Huberman, and Saldana (2014). There are four ways affecting Javanese language maintenance in the Dusun Kampung Banjar namely; There are four ways to maintain Javanese language in Dusun Kampung Banjar namely; Acquisition of the language by adults (21.7%), Number of people habitually using the language (34.8%), All age group encourage in the language (26%), and Using a language to next generation (17.4%).